Gendered perceptions and attitudes towards voting in Gweru Urban - Madamombe, Rumbidzai (Midlands State University, 2018)
The main focus of this research study was exploring gendered perceptions and attitudes towards voting in Gweru Urban. The main objectives of the study were to firstly to find out the views of men and women with regards to the process of voter registration in Gweru Urban. Secondly, the study sought to unravel the perception and attitudes of men and women towards voting and its relevance in Gweru Urban. Its last objective was to explore the push factors behind voting for men and women in Gweru Urban. A descriptive research design was used for this study and two research instruments used, namely – questionnaires and interviews. The target population for the study were mainly the man and women in Gweru urban as well as stakeholders in the area. The study findings revealed that men generally have positive attitudes and perceptions with regards to voting in Gweru urban than women. The study recommended that there be more education, gender awareness, more access to information as well as improvement of voting systems to enhance men and women’s participation in voting.